A comparative authentication study of fresh fruit and vegetable juices using whole juice and sugar-specific stable isotopes. (30th March 2022) - Wu, Hao; Zhou, Xiuwen; Chen, Haiquan; Jin, Baohui; Yan, Zhi; Xie, Liqi; Zhou, Haichao; Rogers, Karyne M.; Lin, Guanghui
Highlights: Twenty-one different fresh fruits and vegetables were isotopically characterized. Juice pulp is used as an internal standard to detect added water and sugar. δ 13 C of sugars in juices were used to identify extraneous C3 sugars. δ 18 O of juice water was used to identify pure juice. Stable isotope technology can effectively detect NFC juice adulteration. Abstract: Not-from-concentrate (NFC) juice has better nutrition, flavor and higher price than reconstituted juice. Accordingly, NFC juice is prone to adulteration and is an ongoing industry problem that has not yet been resolved. Undeclared addition of water and sugar are the main forms of NFC juice adulteration. This paper investigates the carbon and oxygen stable isotope ratios (δ 13 C and δ 18 O values) of the bulk juice and different juice components from 21 fruit and vegetable juices, and qualitatively and quantitatively analyzes the addition of water and sugar in NFC juices. The results show that the use of fruit pulp can help to qualitatively and quantitatively indicate the presence of C4 plant sugars in NFC juice, and can reliably detect added C4 plant sugars above 7 %. Sugar-specific isotope analysis (SSIA) technology was used to determine the δ 13 C values of different sugars (sucrose, glucose and fructose) and carbon content to qualitatively infer C3 plant sugar addition. Pulp extracted from juice had a good linear relationship with the juice water δ 18 O values (R 2  >0.90). The addition of water to NFC juice can also be determined by comparing δ 18 O values of extraneous water, pulp and filtered juice. Stable isotope technology confirmed NFC juice adulteration of in-market samples using the pulp as an internal reference and was found to be a useful tool to detect adulteration of in-market NFC juice.